Common Grammatical Syntactic Errors in Tree Diagrams Done by 6th Semester English-Language Majors at Tripoli University: An Analytic Study - Suhair Saad Faraj (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
This analytic study focused on the identification of grammatical syntactic errors in Tree Diagrams, figuring out the underlying reasons for these errors, and addressing these errors through effective teaching strategies. Data were collected through assignments and tests required 6th semester English language students at Tripoli University to represent given sentences using Tree Diagrams. Study findings revealed that students encountered various types of syntactic errors in using Tree Diagrams to represent sentences. The most common errors included the incorrect placement of constituents in the Tree Diagrams, misidentification of the head of a phrase, and improper use of syntactic rules, such as subject-verb agreement. The underlying reasons for these errors were found to be the influence of Arabic syntax on English syntax, limited knowledge of English syntax, and the difficulty of mastering the syntactic rules of English. The study had some pedagogical implications that could contribute to the development of a better understanding of the syntactic difficulties faced by Arab students. It could also provide insights into how these difficulties could be addressed through the implementation of effective teaching strategies in EFL contexts by taking into account of students’ linguistic backgrounds and possible challenges that may impede the smooth transfer of syntactic structures from one language to another.